Are there long-term temporal trends of size composition and the length– weight relationship? Results for chokka squid Loligo reynaudii during the peak spawning season off the south coast of South Africa. Issue 2 (3rd April 2021) - Lipiński, MR; Mmethi, MA; Yemane, D; Githaiga-Mwicigi, J; Sauer, WHH
Abstract : Temporal trends in the size composition (length frequency) and length–weight (L–W) relationship of chokka squid Loligo reynaudii on the south coast of South Africa were assessed over periods spanning 22 years: length frequencies from 1996 to 2017 (with 15 years represented); and L–W relationships over 9 years between 1994 and 2016. To allow for comparison, identical data selection and processing was adopted for all years considered (i.e. identical period of 60 days in spring–summer; the same depths and areas; chokka with empty stomachs; and squid of the same maturity stage). Although there were no significant long-term temporal trends in the mean lengths, there was a significant short-term drop in the mean lengths over the years 2014–2017 (especially in females), which could not be attributed with certainty to any cause. A tentative explanation is that this drop might be linked to the introduction of an additional closed season in these years. The estimated parameters of the L–W relationship also revealed no trend over the years considered. Investigation of the caecum colour, which indicates the state of starvation (white: 8 h on average after food ingestion; yellow: 6 to 7 h after food ingestion), showed significantly more starving males than starving females. Starvation of males on the spawning grounds might be associated with the spawning behaviour of chokka.